Simultaneous determination of multiple neurotransmitters and their metabolites in rat brain homogenates and microdialysates by LC-MS/MS. Issue 9 (7th May 2015) - Zhang, Li-Hong; Cai, Hua-Lin; Jiang, Pei; Li, Huan-De; Cao, Ling-Juan; Dang, Rui-Li; Zhu, Wen-Ye; Deng, Yang
<x xml:space="preserve">Abstract</x> Determination of multiple neurotransmitters and their metabolites in rat brain homogenates and microdialysates.